Consumption and Consumer Preferences of Fresh and Frozen Potatoes in Semarang City - Kansha Fathiya; Wahyu Dyah Prastiwi; Titik Ekowati (Journal of Consumer Sciences, 2024)
Farmers, producers, and other parties involved in the agricultural production chain of vegetable commodities place a high value on knowing consumer preferences when making decisions on developing and manufacturing agricultural food products. This study aims to investigate consumer behavior and identify information on consumer preferences for both fresh and processed (frozen) potatoes. The study was conducted in Semarang City, using a survey method. Purposive sampling method was employed to recruit 100 respondents, aged above 21 years, residents of Semarang City, and had consumed at least fresh and/or frozen potatoes in the last month. A questionnaire using Google Forms was employed to gather data online. It was distributed via social media platforms. The data collected was analyzed by descriptive and conjoint analysis. The results showed that the most frequent consumption was once a week with regular types of fresh potatoes being consumed; the respondents' spending on potato consumption was ≤ IDR 25,000/ month, and they consumed ≤2 kg of potatoes per week. Potato consumer preferences showed that the fresh potato attributes most liked by consumers are large tuber size, smooth skin, and ≤5 lateral buds, with the number of lateral bud attributes being the most prioritized. The most preferred attributes for frozen potatoes are a straight form, priced at IDR 39,000 to 58,000, batter-coated flavor, 801-1000 gr size packaging, and branded, with the shape attribute being the most prioritized. These findings suggest that farm producers can develop innovative potato varieties with fewer lateral buds and shapes for frozen potatoes.